Clinical value of mean platelet volume in predicting and diagnosing pre-eclampsia: a systematic review and meta-analysis - Ye, Dan; Li, Shuwen; Ding, Yi; Ma, Zhenqin; He, Rongxia (Frontiers in Cardiovascular Medicine, 2023)
Background Pre-eclampsia (PE) is a severe pregnancy complication. Thrombocytopenia and platelet dysfunction are common hematology disorders in PE. Previous studies considered mean platelet volume (MPV), a functional marker of platelets, as a potentially useful predictor for the diagnosis of PE. Methods PubMed, China Biomedical Literature Database, Chinese National Knowledge Infrastructure, Embase, Wanfang, VIP, and Cochrane Library databases were searched to gather diagnostic trials evaluating the diagnosis of PE using MPV, from their inception to 13 March 2023. We also searched Google Scholar and Baidu. Results A total of 22 studies from 20 articles were found. The pooled diagnostic accuracy of the MPV for PE recognition was as follows: sensitivity (SEN) 0.676 [95% confidence interval (CI) (0.658–0.694)], specificity (SPE) 0.710 [95% CI (0.703–0.717)], and diagnostic odds ratio (DOR) 7.012 [95% CI (4.226–11.636)], and the SROC-AUC and Q* indices were 0.7889 and 0.7262, respectively. The pooled SEN, SPE, and DOR of the diagnostic accuracy of MPV for PE before 16 weeks of gestation were 0.707 [95% CI (0.670–0.743)], 0.639 [95% CI (0.611–0.667)], and 4.026 [95% CI (2.727–5.943)], and the SROC-AUC and Q* indices were 0.7278 and 0.6753, respectively. For the interval of truncation values between 9 and 10 fl, the SROC-AUC and Q* indices for MPV were 0.8856 and 0.8162, respectively. Conclusions Available evidence suggests that MPV has a moderate predictive and diagnostic value for PE, particularly in diagnosing after 20 weeks of gestation. The diagnostic accuracy is higher when the MPV cut-off falls between 9 and 10 fl. The sensitivity of MPV alone in diagnosing PE is not high, and the combination of other markers for predictive diagnosis may better differentiate PE. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023425154, identifier: CRD42023425154.